2018
DOI: 10.1101/366732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden in plain sight - highly abundant and diverse planktonic freshwater Chloroflexi

Abstract: 21Background: Representatives of the phylum Chloroflexi, though reportedly highly abundant (up to 22

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 71 publications
1
11
1
Order By: Relevance
“…nov.) within the ‘Patescibacteria’ group, and ‘ Candidatus Aquadulcis frankliniae’ gen. nov. sp. nov., represented by WB4_1_0576 (GenBank: RFPZ00000000), from a novel genus within the recently described class ‘ Candidatus Limnocylindria’ (Mehrshad et al ., 2018) (‘Chloroflexi’). Additional description of these taxa including protologues is available as Supplementary Material (Text S3 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…nov.) within the ‘Patescibacteria’ group, and ‘ Candidatus Aquadulcis frankliniae’ gen. nov. sp. nov., represented by WB4_1_0576 (GenBank: RFPZ00000000), from a novel genus within the recently described class ‘ Candidatus Limnocylindria’ (Mehrshad et al ., 2018) (‘Chloroflexi’). Additional description of these taxa including protologues is available as Supplementary Material (Text S3 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BQH has been used to explain the genome reduction of taxa with large population size (small effective population sizes are typically used to explain genome reductions such as those observed in endosymbionts), as observed in the marine members of the genera ‘ Ca . Pelagibacter’ and Prochlorococcus (Morris et al ., 2012; Giovannoni et al ., 2014) as well as in freshwater microorganisms including members of ‘Actinobacteria’ and ‘Chloroflexi’ (Mehrshad et al ., 2018; Neuenschwander et al ., 2018). Here, we show that the effects predicted by BQH may be observed across Bacteria .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomeresolved studies focusing on other ubiquitous lineages, such as LD12 (Alphaproteobacteria) and acI (Actinobacteria), have also shown that geographically isolated lakes are generally inhabited by distinct species (i.e., ANI < 95%) [39,40]. Meanwhile, genomes sharing ANI > 95% were isolated from lakes located up to hundreds of kilometers apart and separated by the Alps [41,42] and even between lakes on different continents [40,43,44]. No global phylogeographic patterns at the phylogenetic resolutions of ITS [45] and ANI [46] were observed for Microcystis, ubiquitous bloom-forming freshwater cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%